The Role of Habit Changing in Peirce’s Evolutionist Pragmatism - Santaella, Lucia (2013)
After 1900, Peirce engaged himself in the development of his theory of signs, particularly in the theory of interpretants and even more specifically in the theory of the logical interpretants, since the latter represented the touchstone for linking pragmatism to the theory of signs. In 1907, he declared that the problem of what the “meaning” of an intellectual concept is could only be solved by the study of the interpretants, or the proper significate effects of signs. It was within this concept that Peirce developed his famous subdivision of interpretants in emotional, energetic and logical. Peirce stated in 1968 that the interpretant of a thought is another thought, and that this process, theoretically, is infinite. Many authors impressed with this assertion, and without bothering to follow the progress of this concept throughout Peirce’s works, favored that infinite semiosis, so often referred to. Umberto Eco, for instance, was one author who made extensive use of this notion of infinitude. The aim of this paper is to discuss the transformation that this concept of interpretant has undergone in Peircean works, particularly after 1907, when Peirce introduced his notion of the logical interpretant. This notion would come to change the idea – which unfortunately continues widespread – that semiosis is an abstract infinite process, unconnected with human action. Were it so, semiosis would bear no relation with pragmatism. When Peirce discovered the role of the logical interpretant in habit, and of the ultimate interpretant in the change of habit, he combined the processual nature of semiosis with pragmatism. From this synthesis derived the evolutionist character of his pragmatism.